Potensi Ketersediaan Air Untuk Memenuhi Kebutuhan Air Baku Saat Ini (2019) Dan Proyeksi 20 Tahun Rencana (2038) Di Kabupaten Manggarai Timur - Sutikno ; Khaerudin, Dian Noorvy ; Sulistyani, Kiki Frida (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Clean water plays an important role in meeting basic human needs. One of them is used for household purposes as drinking water. The Borong watershed (DAS) has an area of around 119.37 km2. The Borong watershed covers two districts on Flores Island, Manggarai Regency and East Manggarai Regency. Along with increasing population growth which will also be followed by improved economic, social and educational conditions of a community, there will be an increase in water demand. The purpose of this study is to determine the availability of water to meet current raw water needs (2019) and projections for the next 20 years (2038) in East Manggarai Regency. The process of collecting data is done by calculating hydrological, climatological, and population data. The results of the analysis of the calculation of the probability of 90% obtained the average mainstay available at Wae Musur 1 and 2 free intakes of 3.64 million m? / month. Analysis of the water balance for raw water needs (domestic water) experienced a surplus ranging from 1.40 million m? / month to 6.45 million m? / month.